The Irish Janus on his way to the House of Peers conducted by the Dublin Populace. - (:unkn) unknown (My University, 1799)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Grattan, Henry, 1746-1820.; Ireland -- Politics and government -- 1760-1820 -- Caricatures and cartoons